Pengaruh Penggunaan Model Blended Learning Tipe Station Rotation Terhadap Berpikir Kritis Peserta Didik Pada Materi Struktur Bumi dan Perkembangannya - Ananda Uswatun Ummah; Lukman Nulhakim; Trian Pamungkas Alamsyah (PendIPA Journal of Science Education, 2025)
This study aimed to examine the use of a mixed learning model of station rotation on the critical thinking skills of junior high school students with the science material of Earth Structure and Its Development. This study uses a quantitative method, a quasi-experimental design with a non-equivalent control group design. Two classes were used, one experimental class and one control class, each of which used a different learning model. The sampling technique used was non-probability sampling or non-random sampling, with the type of sampling being purposive sampling. The results showed that the discovery learning model had a greater influence on students' critical thinking skills compared to the mixed learning model of station rotation. After conducting research and data analysis, a result was obtained that there was no effect of the use of a mixed learning model of station rotation on students' critical thinking skills on the material of Earth Structure and Its Development. These result were obtained from a non-parametrik test (Mann Whitney test), namely the Assymp.2 sig(2 tailed) value of 0,151 > 0,05 which can be said to reject the research hypothesis.